Analysis of land use effect on the structural diversity of Tamaulipan thornscrub - Jiménez-Pérez, Javier; Alanís-Rodríguez, Eduardo; Aguirre-Calderón, Óscar; Pando-Moreno, Marisela; González-Tagle, Marco (Instituto de Ecología, A.C., 2016)
The effect of land use on the structural diversity of Tamaulipan thornscrub in northeastern Mexico was examined. The objective was to determine whether land use modified diversity, ecological indicators, structural and vertical distribution of trees and shrubs. The analysis was performed by comparing three ecosystems with different land use history: extensive cattle grazing, traditional agriculture and clear cutting with 21 year of abandonment. The methodology used was a combination of rectangular sites and a sampling analysis called "structural group of four trees". Results showed differences in diversity, ecological indicators, vertical distribution and dimensional structure.